La Responsabilidad social empresarial como Base de la Estrategia Competitiva del Puerto de Santa Marta (2021)
This work proposes a theoretical analysis of Corporate Social Responsibility (CSR) as a strategy for the competitiveness of the company Sociedad Portuaria de Santa Marta (SPSM). With the objective of exploring whether its application responds to the purpose of being a responsible company or is a strategy for competitiveness. The methodology used was based on a literature review with SPSM management reports, books and secondary information sources. The results show that, in the market, companies are beginning to adopt CSR as part of their business strategies, given the obligation to integrate into society in order to establish a better environment to operate competitively. The conclusion shows how SPSM through CSR has been implementing a strategy of competitive advantage in the short and long term, of permanence of the company in the market, a strategy masked in the social commitment to society.